The grand delusion : Britain after sixty years of Elizabeth II - Haseler, Stephen, 1942- (London : I. B. Tauris, 2012)
In this groundbreaking new book, Stephen Haseler argues that the class structure which the monarchy has continued to encourage has retained outdated, yet seemingly entrenched, attitudes which have negatively affected Britain's economy, capacity to innovate, and international stature.
Includes bibliographical references and index.
Keywords: Monarchy -- United Kingdom; Great Britain -- Politics and government -- 1945-; Great Britain -- History -- Elizabeth II, 1952-; Great Britain -- Social conditions -- 21st century